Description of a new group of species of Edessa Fabricius, 1803 (Hemiptera: Pentatomidae: Edessinae) with translucent spot on hemelytra - Campos, Breno Batista; Nunes, Benedito Mendes; Bitar, Murilo Victor Silva; Fernandes, Jose Antonio Marin (Zootaxa, 2020)
Several species of Edessinae, especially Edessa, were described from Central America in classic and recent works; but fauna from this region still has many groups of species with remarkable characteristics to be described. One of these groups is herein described to include species with part of the corium weakly pigmented and translucent. The group E. stalii is composed by Edessa stalii and three new species: E. translucida sp. n., E. bryoviridis sp. n. and E. brunneofasciata sp. n. Diagnoses, measurements, photographs, and a map of distribution are presented.